Assessment of women who applied for the uterine transplant project as potential candidates for uterus transplantation. Issue 1 (17th September 2014) - Erman Akar, Munire; Ozekinci, Murat; Alper, Ozgul; Demir, Durkadin; Cevikol, Can; Meric Bilekdemir, Asli; Daloglu, Aylin; Ongut, Gozde; Senol, Yesim; Ozdem, Sebahat; Uzun, Gulbahar; Luleci, Guven; et al.
Abstract Aim To review the medical charts of women who applied for the uterine transplant project from June 2008 to June 2011 in our hospital retrospectively (18–40 years). Methods The data for 144 women were retrieved, and information was collected on the etiology of uterine factor infertility(UFI); ovarian reserve tests; and accompanying anatomic, infectious, genetic and endocrinological problems. Results There were 119 patients with primary amenorrhea and uterovaginal agenesis and 25 patients with a history of hysterectomy. The complete Müllerian agenesis patients formed the largest group of the UFI patients with better anti‐Müllerian hormone levels and antral follicle count. Anatomical anomalies such as a solitary pelvic kidney may accompany Mayer–Rokitansky–Kuster–Hauser syndrome (MRKH) and impede surgery. The mean ages in MRKH, hysterectomy and complete androgen insensitivity syndrome (CAIS) cases were 24.7, 35.0 and 34.4 years, respectively. The karyotype analysis showed 46XX (MRKH) in 109 patients and 46XY (CAIS) in 10 of the primary amenorrhea patients. Conclusion Hysterectomy may deteriorate ovarian blood flow and decrease ovarian reserve. Fertility preservation may be considered in young woman undergoing hysterectomy.